Demand and Equilibrium Price of Health Care: A Structural Equation Approach - Firano Zakaria; Elhamyani Abdelilah; El Marzouki Abdenbi (Foundations of Management)
In this article, we propose a new approach to estimating health-care demand. The aim of this paper is to determine the production costs of health care from the demand function of care. To do this, we used an approach based on structural equations where consumption and demand are estimated to capture the dynamics of health costs within a self-managed public hospital. Following this approach, based on the equilibrium between supply and demand of health care, we used the social and professional characteristics of beneficiary to estimate the demand function, which will approximate the cost of health care. The results showed that the demand for care is largely dependent on economic, demographic, and perception factors. Also, the back testing and corroboration tests of the predictions affirm that the functions developed will allow a better cost forecast for the hospital unit, able to propose a budgetary and partial cost approach in the future. Some limitations can be mentioned in connection with the accessibility to accounting data and also the ignorance of time dimension or dynamic evolution of cost demand.